Tindak Tutur Asertif dalam Podcast Deddy Corbuzier yang berjudul “Ghozali Everyday NFT Kaya Mendadak? - Afni, Renni; Ningsih, Rika (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2025)
This study aims to describe the form of assertive speech acts in Deddy Corbuzier's podcast entitled "Ghozali Everyday NFT Kaya Mendadak?". Podcasts were chosen as the object of study because they are a popular communication media that combines elements of entertainment, education, and social interaction. This study uses a qualitative descriptive approach with a pragmatic analysis method based on the theory of speech acts by Searle (1979). Data in the form of speech from hosts and sources were analyzed to identify types of assertiveness. Data collection techniques used the listening and note-taking technique. The results of the study showed that there were assertive speech acts used to convey information, express opinions, provide clarification, and share personal experiences in the form of speech acts stating, informing, suggesting, explaining, showing, demanding, and complaining. The speech act that dominates is the speech act of informing, indicating that the main purpose of communication in this podcast is to convey information and build listener trust in the source. This study is expected to contribute to authentic material to analyze the real context of language use in popular media, thereby helping students understand the dynamics of language use in contemporary digital communication.